2011
DOI: 10.1111/j.1465-7295.2009.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

What Is Happening to the Impact of Financial Deepening on Economic Growth?

Abstract: Although the finance-growth relationship is now firmly entrenched in the empirical literature, we show that it is not as strong in more recent data as it was in the original studies with data for the period from 1960 to 1989. We consider two related explanations. First, excessive financial deepening or too rapid growth of credit may have led to both inflation and weakened banking systems which in turn gave rise to growthinhibiting financial crises. Second, excessive financial deepening may be a result of wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
269
0
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(309 citation statements)
references
References 29 publications
28
269
0
12
Order By: Relevance
“…Finally, addressing similar questions as Loayza and Ranciere (2006), but using a somewhat different approach, Rousseau and Wachtel (2011) show that the impact of financial deepening on growth is not as strong with more recent panel data (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) as for the period from 1960 to 1989. They posit that the rapid growth of credit and widespread liberalization in the nineties led to both inflationary pressures and a weakening of the banking system that ultimately triggered financial crises, which are responsible for "the disappearance of the finance effect".…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, addressing similar questions as Loayza and Ranciere (2006), but using a somewhat different approach, Rousseau and Wachtel (2011) show that the impact of financial deepening on growth is not as strong with more recent panel data (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) as for the period from 1960 to 1989. They posit that the rapid growth of credit and widespread liberalization in the nineties led to both inflationary pressures and a weakening of the banking system that ultimately triggered financial crises, which are responsible for "the disappearance of the finance effect".…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dynamic panel threshold estimation results of equation (6) Rousseau and Wachtel, 2011;Law and Singh, 2014, among others). As for control variables, almost all variables used in the threshold model have coefficients similar to those we obtained in our previous finding with the exception of fixed capital formation and population.…”
Section: B2 Robustness Check Using Panel Threshold Model 32mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was found that this relationship is positive only when inflation is below 5% [Rousseau, Wachtel 2002]. It was also proven that their relationship is weaker in developing countries and might has weakened further over the years [Rousseau,Wachtel 2011].…”
Section: Financial Development Concept and Its Links With Economic Grmentioning
confidence: 97%
“…1 A number of other results have suggested that the empirical evidence is not consistently positive, however. Important variations have been shown to exist in the significance and direction of finance-growth connection across countries (Demetriades and Hussein, 1996), across stages of development (Rioja and Valev, 2004), and across time (Rousseau and Wachtel, 2010).…”
Section: Introductionmentioning
confidence: 99%